Islamic hire-purchase in Malaysian financial institutions: a comparative analytical study - Abdullah, Nurdianawati Irwani (2005)
Islamic hire-purchase (Ydrah wa-iqtind) is one of the latest innovative products of Islamic banks designed to meet the current demand and avoid certain risks in the financing of consumer durables and motor vehicles. No wonder, this transaction is not acknowledged in the classical jurisprudence, but contemporary scholars have developed its structure through a careful combination of Yarah and sale contracts. In Malaysia, this concept refers to AI-Ijdrah Thumma Al-Bay'(AITAB) and it has grown in popularity and continuously expanded partly due to the heightened demand by customers. Since its first inception more than 10 years ago, AITAB has been governed by the Hire-Purchase Act 1967 (HPA), but HPA has received much criticism amongst the practitioners and Shadah experts, who assert the insufficiency of HPA to govern the AITAB transaction when dealing with Shadah issues. Consequently, Mu'amalah Hire-Purchase Bill has been proposed to the Malaysian government to overcome certain limitations of HPA. This study aims to examine the Islamic hire-purchase operation and its regulatory framework in Malaysia. Thorough examination and analysis would help identifying potential strengths and weaknessesin herent in the HPA and how the proposed Bill could provide remedies to various impediments, and offer an alternative regulation to govern the Islamic hire-purchase transaction. To illuminate our understanding of the actual operation of Islamic hire-purchase, this study incorporates in-depth interviews together with a questionnaire survey. A total of 46 in-depth interviews have been conducted on Islamic bankers, SharVah advisors, Shadah scholars, economists, legal experts and government officers. This is further complemented by a country-wide questionnaire survey successfully obtained from 203 customers, aiming at eliciting their perceptions and expectations towards Islamic hire-purchase products. The combination of theoretical discussion on Islamic hire-purchase together with the empirical surveys using both qualitative and quantitative methodology have proved to yield a valuable insight into the revaluation of the Malaysian regulatory system of AITAB. The findings of this study reveal the need to incorporate SharTah principles into the existing Hire-Purchase Act 1967, instead of establishing an independent SharTah law to govern the Islamic hire-purchase operation. It also reveals that customers of Islamic financial institutions in Malaysia have positive views of ArFAB.